2011
DOI: 10.1080/07060661.2011.619828
|View full text |Cite
|
Sign up to set email alerts
|

Powdery mildew (Leveillula taurica) on greenhouse and field peppers in Ontario – host range, cultivar response and disease management strategies

Abstract: Leveillula taurica was observed on field pepper at various sites in south-western Ontario in [2005][2006][2007]. The field isolates collected from these sites were similar to a greenhouse isolate based on morphological observations. Host range of greenhouse and field isolates was similar, with minor sporulation on potato, carrot and several weeds. The greenhouse pepper cultivar 'Samanta' was the most susceptible to L. taurica while 'Triple 4', 'Duplo' and 'Bosanova' were the least susceptible to infection. Bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…Jones et al 2009;Glawe et al 2010;He et al 2012;Romberg et al 2014;García-Gaytán et al 2016;Choi et al 2019). Moreover, Cerkauskas et al (2011) reported significant morphological differences in size between L. taurica isolates from greenhouse-grown peppers and fieldgrown peppers. All of these imply that even in the same host plant, L. taurica may display morphological variations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Jones et al 2009;Glawe et al 2010;He et al 2012;Romberg et al 2014;García-Gaytán et al 2016;Choi et al 2019). Moreover, Cerkauskas et al (2011) reported significant morphological differences in size between L. taurica isolates from greenhouse-grown peppers and fieldgrown peppers. All of these imply that even in the same host plant, L. taurica may display morphological variations.…”
Section: Discussionmentioning
confidence: 91%
“…Yield losses caused by L. taurica reachs up to 40% in pepper production in Puerto Rico (Negron et al 1991). Infection rate of the fungus can reach 100% in pepper plants in Canada (Cerkauskas et al 2011). Infections of L. taurica begin as small chlorotic spots on lower leaves in pepper plants.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, powdery mildew of tomato caused by Oidium neolycopersici L. Kiss is one of the most important diseases which reduce production and quality of the produce. The powdery mildew is a dangerous pathogen, which spread through temperate areas of the world and the disease can cause up to 50 per cent yield losses in tomato (Cerkauskas et al, 2011). The host range of the pathogen is broad and it is reported to attack over 60 species in 13 plant families, particularly members of Solanaceae and Curcubitaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Leveillula taurica , an obligate fungal plant pathogen belonging to the ascomycetes, causes powdery mildew in various vegetable crops, resulting in significant quality and yield losses. In the past few decades, the incidence of L. taurica powdery mildew has been increasing in both greenhouse- and open field-grown peppers worldwide (Damicone, 2009 ; Sudha and Lakshmanan, 2009 ; Cerkauskas et al, 2011 ). Premature defoliation caused by powdery mildew severely reduces crop yields and makes fruits unfavorable for marketing.…”
Section: Introductionmentioning
confidence: 99%